Comparative Study of Performance of SBI Mutual Fund, HDFC Mutual Fund and Birla Sun Life Fund-Growth Schemes: Analyzing the Performance of Mutual Funds in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The performance of mutual funds in India in the initial phase was not even closer to satisfactory level. People rarely understood, and of course investing was out of question. But yes, some 24 million shareholders were accustomed with guaranteed high returns by the beginning of liberalization of the industry in 1992. This good record of UTI became marketing tool for new entrants. The expectations of investors touched the sky in profitability factor. However, people were miles away from the preparedness of risks factor after the liberalization. Secondary data has been used for achieving the objectives of the study.